2021
DOI: 10.1002/ijgo.13583
|View full text |Cite
|
Sign up to set email alerts
|

Detection of high‐risk human papillomavirus infection and treatment of high‐grade vaginal intraepithelial neoplasia: A single‐institution study

Abstract: Objective To identify high‐risk HPV (hrHPV) genotypes associated with high‐grade vaginal intraepithelial neoplasia (VaIN), and evaluate the efficacy of various treatments for high‐grade VaIN. Methods A retrospective review of outcomes among women diagnosed with VaIN after vaginal punch biopsy conducted due to an abnormal Papanicolaou smear or positive test for hrHPV at a hospital in Seoul, Korea, from 2013 to 2018. Logistic regression was used to identify variables associated with abnormal pathologic outcomes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
1
6
0
1
Order By: Relevance
“…It has been reported that there is a positive correlation between the grade of VaIN and grade of concomitant CIN, although there is a non-negligible number of women in whom vaginal lesions were found to be more severe than cervical lesions [ 52 ]. As especially HPV 16 and HPV 31 were found to be highly associated with high-grade VaIN, it is advisable to be particularly attentive for signs of VaIN among patients tested positive for these hrHPV subtypes [ 53 ]. However, to add another degree of complexity, recent data suggests that concomitant CIN and VaIN in the same patient develop independently, since in the great majority of cases different hrHPV types were identified within the cervical and vaginal lesions [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that there is a positive correlation between the grade of VaIN and grade of concomitant CIN, although there is a non-negligible number of women in whom vaginal lesions were found to be more severe than cervical lesions [ 52 ]. As especially HPV 16 and HPV 31 were found to be highly associated with high-grade VaIN, it is advisable to be particularly attentive for signs of VaIN among patients tested positive for these hrHPV subtypes [ 53 ]. However, to add another degree of complexity, recent data suggests that concomitant CIN and VaIN in the same patient develop independently, since in the great majority of cases different hrHPV types were identified within the cervical and vaginal lesions [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…And most of them are considered to be skip lesions rather than a contiguous lesion, because 3 out of 4 VaIN3 recurrent cases are margin negative at the initial surgery. As for VaIN 3, HPV 16, 31 and 52 have been reported to be more involved in its development, 14,[21][22][23] which are slightly different from CIN2/3 (HPV 16 and 18 dominant). It is possible that subtle differences regarding hrHPV may be involved.…”
Section: Discussionmentioning
confidence: 99%
“… 81 In a retrospective review of 389 patients, those who underwent primary laser therapy, brachytherapy, or vaginectomy experienced high rates of remission in histopathologic follow-up (73.7%, 71.4%, and 100%, respectively) and similar rates of hr-HPV clearance (52.6%, 57.1%, and 50.0%, respectively). 114 …”
Section: Methodsmentioning
confidence: 99%
“…There was also no significant influence in the relapse rate by VaIN grading, simultaneous CIN or vulvar intraepithelial neoplasia, previous therapy, or history of hysterectomy 81 . In a retrospective review of 389 patients, those who underwent primary laser therapy, brachytherapy, or vaginectomy experienced high rates of remission in histopathologic follow-up (73.7%, 71.4%, and 100%, respectively) and similar rates of hr-HPV clearance (52.6%, 57.1%, and 50.0%, respectively) 114 …”
Section: Methodsmentioning
confidence: 99%